Latent profile analysis of symptoms of depression and anxiety among perimenopausal women and their predictors - Jiang, Minhui; Chen, Liang; Zheng, Xiaomin; Feng, Yaling (Frontiers in Psychiatry, 2025)
PurposeThis study aims to consider the latent profiles of depression and anxiety symptoms in perimenopausal women and determine the influencing factors of this classification.MethodsLatent profile analysis was used to explore the subgroups of mental health in perimenopausal women (n=1242, age = 52.55 ± 3.32 years), followed by univariate analysis and multinomial logistic regression to investigate the relationship between sociodemographic, lifestyle, social interaction, perimenopausal symptom factors, and the latent profiles.ResultsDepression and anxiety symptoms in perimenopausal women were classified into three subgroups: “low symptom group” (n=702, 56.5%), “depression and anxiety borderline symptom group”(n=419, 33.7%), and “severe depression and anxiety comorbidity group”(n=121, 9.8%). Additionally, empty nest, chronic diseases, history of mental illness, sleep quality, and perimenopausal symptoms were identified as risk factors for depression and anxiety, while enrolling in urban resident medical insurance and participating in social activities were protective factors.ConclusionThis study identified the heterogeneous characteristics of mental health in perimenopausal women to help provide more targeted screening, personalized interventions and treatment strategies, which are of significant importance in improving the quality of life for perimenopausal women.